Topological Abnormalities of Pallido-Thalamo-Cortical Circuit in Functional Brain Network of Patients With Nonchemotherapy With Non-small Cell Lung Cancer - Liu, Siwen; Yin, Na; Li, Chenchen; Li, Xiaoyou; Ni, Jie; Pan, Xuan; Ma, Rong; Wu, Jianzhong; Feng, Jifeng; Shen, Bo (Frontiers in Neurology, 2022)
Introduction: Some previous studies in lung cancer patients have mainly focused on exploring the cognitive dysfunction and deficits of brain function associated with chemotherapy. However, little is known about functional brain alterations that might occur prior to chemotherapy. Therefore, this study aimed to evaluate brain functional changes in non-chemotherapy patients before chemotherapy with non-small cell lung cancer (NSCLC). Methods: Resting‐state functional magnetic resonance imaging data of 35 NSCLC patients and 46 matched healthy controls (HC) were acquired to construct functional brain networks. Graph theoretical analysis was then applied to investigate the differences of the network and nodal measures between groups. Finally, receiver operating characteristic (ROC) curve analysis was performed to distinguish between NSCLC and HC. Results: Decreased nodal strength was found in the left inferior frontal gyrus (opercular part), inferior frontal gyrus (triangular part), inferior occipital gyrus and right inferior frontal gyrus (triangular part) of patients with NSCLC while increased nodal strength was found in the right pallidum and thalamus. NSCLC also showed decreased nodal betweenness in the right superior occipital gyrus. Different hub regions distribution was found between groups, however, no hub regions showed group-differences in the nodal measures. Furthermore, ROC curve analysis showed good performance in distinguishing NSCLC from HC. Conclusion: These results suggested that topological abnormalities of pallido-thalamo-cortical circuit in functional brain network might be related to NSCLC prior to chemotherapy, which provided new insights concerning the pathophysiological mechanisms of NSCLC and could serve as promising biological markers for the identification of NSCLC patients.